Ensuring the Security of Civil Aviation against the Terrorist Phenomenon in the Legislation of the European Union - Cauia, Alexandr; Bria, Feodor (Journal of Danubian Studies and Research, 2022)
The European Union is a supranational structure and is an important part of the global civil aviation market. Terrorist acts are the most dangerous challenge to civil aviation security in the 20th and 21st centuries. Ensuring civil aviation security is one of the key priorities of the member states in particular and the European Union in particular. This article reflects attempts to regulate the process of preventing the negative effects of the terrorist phenomenon on the process of ensuring civil aviation security in the European Union. Following the tragic events of September 11th, 2001 in the United States, the process of regulating civil aviation security in the European Union has rapidly developed. Subsequent attempts to carry out terrorist attacks on civilian aircraft, as well as world experience, have contributed to the awareness of the need to regulate this process at the supranational level. The systemic analysis of the legal norms at the level of the European Union that have as object of regulation the assurance of the civil aviation security is the analysis object of this research.